Comparison of prehospital resuscitation quality during scene evacuation and early ambulance transport in out-of-hospital cardiac arrest between residential location and non-residential location. (January 2023) - Choi, Seulki; Kim, Tae Han; Hong, Ki Jeong; Lee, Stephen Gyung Won; Park, Jeong Ho; Ro, Young Sun; Song, Kyoung Jun; Shin, Sang Do
Abstract: Background: High-quality prehospital cardiopulmonary resuscitation (CPR) is important for out-of-hospital cardiac arrest (OHCA). We aimed to evaluate prehospital CPR quality during scene evacuation and early ambulance transport in patients with OHCA according to the type of cardiac arrest location. Methods: This retrospective observational cohort study enrolled patients with non-traumatic adult OHCA in Seoul between July 2020 and March 2022. Prehospital CPR quality data extracted from defibrillators were merged with the national OHCA database. The location of cardiac arrest was categorized into two groups (residential and non-residential). CPR quality indices including no-flow (any pause >1.5 s) fraction were compared according to the type of arrest location at each minute of EMS scene evacuation and early ambulance transport (5 min prior to 5 min after ambulance departure). Results: A total of 1, 222 OHCAs were enrolled in the final analysis after serial exclusion. A total of 966 OHCAs (79.1%) occurred in the residential areas. The CPR quality deteriorated during the scene evacuation in both location type. The mean no-flow fractions were significantly higher in residential places than in non-residential places. The mean proportion of adequate compression depth and rate was lower in cardiac arrests in residential places. The discrepancy in EMS CPR quality during scene evacuation was more prominent when mechanical CPR devices were not used. Conclusion: Deterioration of CPR quality was observed just before and during early ambulance transport, especially when the cardiac arrest location was a residential area or when only manual CPR was provided.